1996
DOI: 10.1016/s1074-7613(00)80293-9
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Eotaxin Expression Parallels Eosinophil Accumulation during Lung Allergic Inflammation but It Is Not Restricted to a Th2-Type Response

Abstract: A model of lung eosinophilia based on the repeated exposure of mice to aerosolized OVA has been used to identify C-C chemokine genes expressed at stages of massive eosinophil infiltration. We describe the identification and cloning of a cDNA that encodes a mouse C-C chemokine with 68% amino acid identity to guinea pig Eotaxin. The recombinant protein encoded by this gene displays potent and specific chemotactic activity for eosinophils, both in vivo and in vitro. Its mRNA levels parallel the kinetics of eosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
169
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(174 citation statements)
references
References 55 publications
5
169
0
Order By: Relevance
“…Using animal models of allergic airway inflammation, there is now considerable evidence to support the hypothesis that eotaxin plays an important role in eosinophil homing and tissue recruitment (28 -30). Indeed, eotaxin mRNA and/or protein expression is up-regulated in guinea pig and rodent models of allergic asthma that parallel eosinophil accumulation (31)(32)(33). It was further shown that a neutralizing Ab to eotaxin induced a significant inhibition of eosinophil infiltration following Ag challenge (32) and eotaxin knockout mice exhibited a significantly reduced eosinophil recruitment to the lung 18 h after allergen challenge (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Using animal models of allergic airway inflammation, there is now considerable evidence to support the hypothesis that eotaxin plays an important role in eosinophil homing and tissue recruitment (28 -30). Indeed, eotaxin mRNA and/or protein expression is up-regulated in guinea pig and rodent models of allergic asthma that parallel eosinophil accumulation (31)(32)(33). It was further shown that a neutralizing Ab to eotaxin induced a significant inhibition of eosinophil infiltration following Ag challenge (32) and eotaxin knockout mice exhibited a significantly reduced eosinophil recruitment to the lung 18 h after allergen challenge (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…10C). Eotaxin is well recognized as a potent chemoattractant for eosinophils (46,47). Although eosinophil accumulation was not compared in WT versus Tbx21 2/2 mice, it has previously been reported that Ghanian pediatric patients with CM had uniformly low eosinophil counts because of tissue sequestration and destruction rather than decreased production during acute illness followed by eosinophilia 30 d after cure (48).…”
Section: Figurementioning
confidence: 99%
“…Eotaxin is a fundamental regulator of physiological eosinophil trafficking during healthy states [23] and inflammation [24]. Ecalectin (galectin-9), which is produced by antigen-stimulated T cells, is a powerful eosinophil-specific chemoattractant in vitro and in vivo [25].…”
Section: Eosinophil Migration and Infiltration To Tissuesmentioning
confidence: 99%